Adverse outcome of coarctation stenting in patients with Turner syndrome. Issue 2 (15th September 2016) - van den Hoven, Allard T.; Duijnhouwer, Anthonie L.; Eicken, Andreas; Aboulhosn, Jamil; de Bruin, Christiaan; Backeljauw, Philippe F.; Demulier, Laurent; Chessa, Massimo; Uebing, Anselm; Veldtman, Gruschen R.; Armstrong, Aimee K.; van den Bosch, Annemien E.; et al.
Abstract : Objectives: This study examines the outcome and procedural outcomes of percutaneous stent angioplasty for aortic coarctation in patients with Turner syndrome (TS). Background: TS occurs in 1 in 2, 500 live‐born females and is associated with aortic coarctation. Methods: In this multicenter, retrospective cohort study, all patients with TS and a coarctation of the aorta, treated with percutaneous stent implantation were included. The procedural strategies were dictated by local protocols. Adverse events at short‐ and long‐term follow‐up and qualitative parameters concerning the stent implantation were assessed. Results: In the largest study to date of TS patients receiving aortic stents, a total of 19 patients from 10 centers were included. Twelve patients were treated for native and 7 for recurrent coarctation. Age at intervention was 16.9 (7–60) years (median; min–max). The coarctation diameter increased significantly from 8.0 mm (2–12) pre‐intervention to 15.0 mm (10–19) post‐intervention ( P  < 0.001). Three (15.8%) adverse events occurred within 30 days of the procedure, including two dissections despite the use of covered stents, one resulting in death. At long‐term follow‐up (6.5 years, min–max: 1–16), two additional deaths occurred not known to be stent‐related. Conclusions: Though percutaneous treatment of aortic coarctation in TS patients is effective, it is associated with serious morbidity and mortality. These risks suggest that alternative treatment options should be carefully weighed against percutaneous stenting strategies. © 2016 Wiley Periodicals, Inc.